253 Evaluating paediatric asthma MDTs across London. (17th August 2022) - Elliott, Josephine; Watson, Mando; Goldring, Stephen
Abstract : Aims: Asthma prevalence has been on the rise for the last forty years 1 and it is the most common chronic respiratory disease of childhood. 2 The aim of this pilot study was to provide a forum to facilitate discussion between primary care and asthma specialists, with the overall aim to improve primary care healthcare professionals' confidence in treating paediatric asthma patients. Methods: From September to December 2021, the local Integrated Care System (ICS) ran a pilot of childhood asthma reviews with GP practices. Using data from the Northwest London 'Whole Systems Integrated Care' database, GP practices within Primary Care Networks (PCNs) with 'high-risk' asthma paediatric patients were identified and offered a 1-1.5 hour online multidisciplinary team meeting (MDT) with their local specialists, including a paediatric consultant, an asthma nurse and an asthma pharmacist. Factors that identified patients as 'high-risk' included their number of acute asthma exacerbations within the last 12 months, their use of six or more short-acting beta agonists (eg salbutamol) in the last 12 months, not having had an asthma annual review, and not having a personal asthma plan. A structure, process, outcomes framework was used to evaluate this pilot. Data were collected on the number of MDTs organised, the number of health professionals at each MDT, the topics discussed, and an anonymous mentimeter form collected feedback with a mixture of polls, scales and open-text questions. Results: Within these 15 PCNs, 89 practices within 7 boroughs were offered a multidisciplinary team meeting (MDT), pharmacy support and a patient feedback survey. Twelve MDTs were set up on a first come, first served basis within the pilot timeframe. The average number of healthcare professionals at each MDT was 11 (range of 8-16) and included GPs, Paediatric Consultants, Pharmacists, Nurses, Practice Admin, junior doctors, and medical students. There were 38 feedback responses on mentimeter. This showed that knowledge of who to contact for specialist support increased by 65%, with 57% of attendees feeling more comfortable to contact specialists with queries ( figure 1 ). There was a marked increase in attendees' confidence in diagnosing and managing asthma ( figure 2 ). Overall, the attendees scored the effectiveness and usefulness of these MDTs as 9.6 out of 10 and 9.5 out of 10, respectively. Conclusion: This pilot showed that there is appetite for integrated care and proactive approaches to managing paediatric patients with asthma. These MDTs offer an effective way for building such relationships between primary and secondary care. References: Serebrisky D, Wiznia A. Pediatric Asthma: A global epidemic. Annals of Global Health, 2019;85 :6. Patel S, Teach S. Asthma. Paediatrics in Review, 2019;40 :549-567.